Sarcoid-like disorder of the intracranial optic nerve: Clinicopathological report of two cases - Frisén, L. (1977)
Two cases with a sarcoid-like disorder apparently restricted to the intracranial optic nerve and the adjacent dura mater are described, doublilng the number of reported cases. In both instances there were unilateral visual loss and unusual radiographic changes in the optic canal area. Biopsy samples showed localised infiltration of tissues with non-caseating tubercles containing epithelioid and multinucleated giant cells.